Haemoglobinopathy: considerations for reproductive health. (29th August 2018) - Supramaniam, Prasanna Raj; Mittal, Monica; Hay, Deborah; Narvekar, Nitish; Lim, Lee Nai; Becker, Christian M
Abstract : Key content: An overview is given of the different types of haemoglobinopathies and the effect of iron overload on the function of vital organs, including the endocrine system. Assessment modalities for ovarian and testicular function measurement. Current management options for patients with hypogonadotrophic hypogonadism secondary to iron overload include chelation therapy from an early age and human menopausal gonadotrophin to induce ovulation and spermatogenesis. Egg, sperm or embryo donation remain alternative options in cases refractory to stimulation protocols. Cryopreservation is an option to retain future fertility in some patients with a haemoglobinopathy, but is not standard care. We consider the psychological impact of a haemoglobinopathy and iron overload, and their effects on reproductive health, as well as good medical support by a multidisciplinary team. Learning objectives: To understand the current evidence of the impact of iron overload secondary to a haemoglobinopathy on reproductive health. To evaluate best practice and alternative options in the management of patients with iron overload in a reproductive health setting.